Unveiling Strategies: Empowering Autistic Adult Learners in Higher Education through Inclusive Research Practices - Kevin J Mallary; Adam L McClain (Adult Education Research Conference, 2024)
This qualitative research investigates strategies of autistic adult learners in higher education through participatory methods. Findings reveal nuanced experiences, emphasizing the need for inclusive research to support diverse learners effectively.
Keywords: disability; higher education; autism; participatory research